Discourse bootstrapping: preschoolers use linguistic discourse to learn new words. Issue 1 (20th February 2015) - Sullivan, Jessica; Barner, David
Abstract: When children acquire language, they often learn words in the absence of direct instruction (e.g. 'This is a ball!') or even social cues to reference (e.g. eye gaze, pointing). However, there are few accounts of how children do this, especially in cases where the referent of a new word is ambiguous. Across two experiments, we test whether preschoolers (2‐ to 4‐year‐olds; n = 239) can learn new words by inferring the referent of a new word from the surrounding linguistic discourse. Across two experiments, we show that children as young as 2 can learn a new word from the linguistic discourse in which it appears. This suggests that children use the linguistic discourse in which a word appears to learn new words. Abstract : We show that children as young as two can successfully learn a new word by inferring its relation to the surrounding discourse, although there are important developmental changes in children's ability to learn words from the discourse context. These data show that sophisticated inferential and pragmatic abilities may underlie children's early word learning.